2022
DOI: 10.1002/ehf2.14258
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between haemodynamic indicators and haemogram in patients with heart failure

Abstract: Aims Pulmonary congestion, reduced cardiac output, neurohumoral factor activation, and decreased renal function associated with decreased cardiac function may have various effects on haemograms. The relationship between these factors and haemograms in patients with heart failure has not been sufficiently investigated. Recently, it was suggested that the lungs are an important site for platelet (Plt) biosynthesis and that it is necessary to study the relationship between pulmonary congestion and Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although we tried to use LVEF and NT-proBNP to more objectively reflect the cardiac function and evaluate the effect of deterioration of cardiac function on STP, the results showed that NYHAFC IV had a more positive effect. We have not found relevant studies describing the mechanism of STP after TAVR in patients with heart failure, and recent studies have shown a strong correlation between left ventricular end-diastolic pressure increase and platelet count decrease in patients with heart failure, suggesting that pressure overload of the lung may interfere with the function of the lung as a site of platelet biosynthesis ( 24 ).…”
Section: Discussionmentioning
confidence: 98%
“…Although we tried to use LVEF and NT-proBNP to more objectively reflect the cardiac function and evaluate the effect of deterioration of cardiac function on STP, the results showed that NYHAFC IV had a more positive effect. We have not found relevant studies describing the mechanism of STP after TAVR in patients with heart failure, and recent studies have shown a strong correlation between left ventricular end-diastolic pressure increase and platelet count decrease in patients with heart failure, suggesting that pressure overload of the lung may interfere with the function of the lung as a site of platelet biosynthesis ( 24 ).…”
Section: Discussionmentioning
confidence: 98%
“…The end diastolic pressure was set to 5 mmHg for the entire study population as per the original publication 4 . The range is thought to represent the majority of the study population of which no one suffered severe heart failure, considering that most patients with heart failure maintain a LV end‐diastolic pressure of 5−20 mmHg, and considering that differences in LV diastolic pressures, within reasonable ranges, have little effect on the calculated PV‐loop parameters 14,15 . Brachial sphygmomanometry data was gathered from the CHILL‐MI study result sheets, from the healthy control data sheets, and from clinical patient charts (SOCCER and MITOCARE) in accordance with informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…intervals, respectively. Two-dimensional contours were used in this study because they can be easily visualized [22][23][24].…”
Section: Declarationsmentioning
confidence: 99%